ALGORITMA TIKTOK SEBAGAI MESIN POLARISASI AGAMA: STUDI NETNOGRAFI PADA KOMUNITAS DAKWAH DIGITAL DI INDONESIA - Pertiwi, At’tin Rahmah; Nisa, Iskarimatun; Suryandari, Meity (STKIP Subang, 2026)
This study examines how TikTok’s recommendation algorithm contributes to the formation of religious polarization among Indonesian Muslim users. Using a netnographic approach, the research conducts an in-depth observation of the distribution patterns of da’wah content, user interactions, and the dynamics of echo chambers formed through TikTok’s For You Page (FYP) mechanism. Data were collected through digital observation of 50 active da’wah accounts and analysis of more than 200 TikTok contents over the period of January–March 2026. The results indicate that TikTok’s algorithm tends to reinforce the homogeneity of religious content consumed by users, thereby creating echo chambers that have the potential to intensify religious exclusivism. These findings are analyzed through the framework of Mediatization theory and the principles of Islamic communication, which emphasize the values of tawassuth (moderation) and tasamuh (tolerance). This study provides important implications for the development of digital literacy based on Islamic values in the era of social media platforms.